SINTESIS MCM-41 DENGAN METODE HIDROTERMAL: PENGARUH WAKTU HIDROTERMAL, RASIO CTA/TMA DAN RASIO Si/Al - , MUSTOFA AHDA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The effect of aluminate and tetramethylammonium hydroxide (TMAOH) addition in the MCM-41 synthesis with cetyltrimethylammonium bromide surfactant (CTAB) was studied. MCM-41 was synthesized with molar composition 1 SiO2 : 0.25 CTAB : 0.29 Na2O : 50 H2O with hydrothermal method. Effect of addition of aluminate and the TMAOH was studied at a mol ratio of Si/Al = 23 and 80 in the synthesis of MCM-41, while a mol ratio of CTA/TMA was performed at 1 and 1.25. The effect of aluminate and TMAOH on the characteristics, stability of MCM-41 material and its ability to adsorb methylene blue was also investigated. The results showed that the addition of aluminate and TMAOH decreased the relative intensity but it increased the stability of MCM-41. Use of TMAOH with mol ratio of CTA/TMA = 1 has a better hydrothermal stability with 88% crystallinity after hydrothermal test at 100 ËC for 24 hours. The adsorption capacity of Al-MCM-41 for methylene blue was 4 times more than the MCM-41 and MCM-41 with TMAOH. Adsorption of methylene blue by Al-MCM-41 followed pseudo second order model with the adsorption rate constant of 0.01 g.mg-1.min-1.